(3TQM GdYhGed (B((3GdeFI(B)s - (3jMji Hf fUhM Hf ESQGFjd, GdeYQha H` jMji LdHjs; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s ((3RGhjI GdMGL QLH aj HjdGb s)
(3ChdgG (B:s
(3hHYO, ajbhd jMji GHf fUhM Hf ESQGFjd GYdehG jGeYGTQ WdGH Gdjbjf s
(3BNQgG (B:s
(3adG jSJZfj GdUZjQ hGdcHjQ EP HgG jMUd dge HUjQI aj GdYdhe cdgG ef aVd Gddg JYGdi Cf jLYd eG LeYJg NGdUkG dMVQJg GdehUha HGdcQe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdfMhs